Strategi Komunikasi Pemasaran Affiliator Shopee Dalam Mempromosikan Produk - Esa Laela Noersabila; Atih Ardiansyah; Ari Pandu Witantra (Universitas Serang Raya, 2023)
Problems: Shopee is the most visited e-commerce and has many strategies in marketing, one of which is to create a Shopee affiliate program that can help mutually benefit online stores and affiliates. Currently, the shopee affiliate is a job that is in great demand so that it can benefit online shops at shopee Purpose: The purpose of this study was to to find out the marketing communication strategy of the Shopee Affiliator in promoting the product. Methodology: The research was conducted using a descriptive qualitative approach using data collection techniques through observation, in-depth interviews and documentation studies and in this study there were five informants. Results/Findings: The results of this study indicate that in promoting products, shopee affiliates do not apply several elements of the promotion mix, namely, affiliates do not advertise for a fee, focus on uploading content on Instagram by paying attention to the best time to post, uploaded content in the form of video types, sharing links according to follower requests which are then sent or shared via instastory and direct messages as a direct application. Paper Type: Marketing Communication